A Critical Ethnographic Approach for Understanding How Environmental Factors Shape Experiences of Community Mobility for Older Adults Aging With and Into Vision Loss: A Protocol Paper - Colleen McGrath; Jami McFarland; Elizabeth Mohler; Carri Hand; Debbie Laliberte Rudman; Barb Fitzgeorge; Melanie Stone (International Journal of Qualitative Methods)
The number of older adults diagnosed with vision loss in Canada, and globally, is growing. Older adults with age-related vision loss (ARVL), including macular degeneration, glaucoma, and diabetic retinopathy, experience a reduced capacity to engage with their communities because their opportunities to access and engage with their environments are greatly reduced. This can lead to feelings of abandonment, enhanced fear, and social isolation, which can have determinantal impacts on physical, social, and psychological health and well-being. This critical ethnographic study moves beyond exclusively identifying physical barriers to community mobility, towards addressing the physical, political, social, and pragmatic barriers to community mobility that are limiting for older adults aging with, and into, vision loss. As a research collective consisting of older adults with vision loss, low vision service providers, policy makers, and Blind and sighted academics, we developed a critical ethnographic study which consists of three qualitative interviews. Our protocol outlines how data for this study were collected, including how methods were adapted to support people experiencing vision loss, analyzed, and managed to ensure best privacy practices. We also describe our approach to engaging in reflexive data analysis and interpretation, including collective data analysis sessions.